Pregnancy subsequent to stillbirth: Medical and psychosocial aspects of care. Issue 3 (June 2017) - Fockler, Megan E.; Ladhani, Noor Niyar N.; Watson, Jo; Barrett, Jon F.R.
Abstract : Pregnancy after stillbirth presents unique challenges for families and healthcare providers. Medical surveillance and interventions must be optimized to improve outcomes and provide individualized support for families. A key component of acceptable care is psychosocial support that is delivered in a timely and sensitive manner by care providers with knowledge about the pervasive impact of stillbirth. With the lack of existing evidence to guide care, there is an urgent need for global leadership and research to address knowledge gaps.